An integrated EHR at Northern California Kaiser Permanente - Bornstein, S. (Applied Clinical Informatics, 2012)
As legacy information systems age, transition to newer systems is inevitable, but at times fraught with challenge. This brief article addresses some of the pitfalls, challenges, and benefits we experienced at Kaiser Permanente as we transitioned several key clinical information systems to Epic Systems for our integrated comprehensive Electronic Health Record (EHR).
Keywords: Implementation and deployment; clinical information systems; facilitators and barriers; electronic health records and systems; patient records; telemedicine and telehealth; clinical documentation and communications; integrated information systems